Produzindo autores: conexões entre interação e autoria na produção de textos em sala de aula - Simone Farias Pereira (2003)
This research has as main objective to analyse text production conditions in classroom and its correlation to authorship construction. It has as basis texts conception such as oral and written production which acquires its meaning through interaction context. It basis itself in a social and cultural background of apprenticeship which places the classroom as the providing environment of individuals participation in their knowledge development. Through the adoption of an ethnographic approach research, a year-four-primary-class of an estate school was observed. This analysis was based on oral dialogues established by the class and also in the written work produced by the students throughout the semester. As an outcome, a description of the class routine is presented, which made possible to identify the meaning of constructed actions with the interaction between individuals, and as in relation to the authorship, the identification of given characteristics to its author by the group members. These outcomes may bring changes to the process of teachers developments, once it demonstrates that these discursive practice analyses taken in class provide clues to comprehension assumption of students authorship and in their produced texts.